Pemberdayaan Siswa PKL Dalam Meningkatkan Proses dan Hasil Belajar Siswa Pada Pembelajaran Teknik Energi Angin - Sawaludin Sawaludin (Journal of Classroom Action Research, 2022)
The purpose of this research is to describe the Empowerment of PKL Students in improving the process and learning outcomes in the learning of Wind Energy Engineering Class XI Tesha SMKN 3 Mataram Year of Study 2021/2022. The research method used is a descriptive research method. Research is designed in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The instruments used in this study are observation, tests, and documentation. Data analysis uses descriptive analysis. The results showed that the number of student attendance increased, the number of teacher readiness categories in the Ready indicator was 100%, and the number of student readiness categories in the indicator increased. Learning outcomes after the evaluation of learning from pre-cycle without the empowerment of PKL students to cycle I, then from cycle I to cycle II in the same process the results experienced improvements including an increase in the Cumulative Achievement Index (GPA), sequentially Pre-cycle I-cycle II, entered into the Low-Normal-High Category. Based on the results of research and analysis of data that have been done, it was concluded that the improvement of learning processes and outcomes as indicators showed improvement. So, research empowering PKL students in improving learning processes and outcomes in the learning of Wind Energy Engineering Class XI Tesha SMKN 3 Mataram Year of Study 2021/2022 resulted in effective learning